Peningkatan Hasil Belajar Menulis Teks Laporan Hasil Observasi Melalui Metode Field Trip Siswa Kelas VIII D SMP Negeri 5 Surakarta - Septia, Shofi Dian (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This Classroom Action Research (PTK) aims to improve the quality of learning outcomes in writing observation report texts for class VIII D students at SMP Negeri 5 Surakarta using the field trip method. The subjects of this research were 32 students in class VIII D of SMP N 5 Surakarta for the 2024/2025 academic year, consisting of 18 male students and 14 female students. The object of this research is the ability to write text reports on student observations through the implementation of the learning model Project Based Learning and field trip method. This research was designed in two cycles, namely cycle I and cycle II. The success criteria for this research are determined based on students' achievement of grades in accordance with (KKTP), which was set at 78. The research results showed that learning using the field trip method in cycle I and cycle II succeeded in improving students' writing learning outcomes in compiling the text of the Observation Result Report (LHO). This is proven by the increase in the average student score from 71.5 with a percentage of 41% in cycle I, to 84.6 with a percentage of 81% in cycle II.